Analysis of global Aeromonas veronii genomes provides novel information on source of infection and virulence in human gastrointestinal diseases - Fang Liu; Christopher Yuwono; Alfred Chin Yen Tay; Michael C. Wehrhahn; Stephen M. Riordan; Li Zhang (BMC Genomics, 2022)
Abstract Background Aeromonas veronii is a Gram-negative rod-shaped motile bacterium that inhabits mainly freshwater environments. A. veronii is a pathogen of aquatic animals, causing diseases in fish. A. veronii is also an emerging human enteric pathogen, causing mainly gastroenteritis with various severities and also often being detected in patients with inflammatory bowel disease. Currently, limited information is available on the genomic information of A. veronii strains that cause human gastrointestinal diseases. Here we sequenced, assembled and analysed 25 genomes (one complete genome and 24 draft genomes) of A. veronii strains isolated from patients with gastrointestinal diseases using combine sequencing technologies from Illumina and Oxford Nanopore. We also conducted comparative analysis of genomes of 168 global A. veronii strains isolated from different sources. Results We found that most of the A. veronii strains isolated from patients with gastrointestinal diseases were closely related to each other, and the remaining were closely related to strains from other sources. Nearly 300 putative virulence factors were identified. Aerolysin, microbial collagenase and multiple hemolysins were present in all strains isolated from patients with gastrointestinal diseases. Type III Secretory System (T3SS) in A. veronii was in AVI-1 genomic island identified in this study, most likely acquired via horizontal transfer from other Aeromonas species. T3SS was significantly less present in A. veronii strains isolated from patients with gastrointestinal diseases as compared to strains isolated from fish and domestic animals. Conclusions This study provides novel information on source of infection and virulence of A. veronii in human gastrointestinal diseases.